SUBJECT: URBAN, RURAL, AGRICULTURE AND ECOLOGICAL INDUSTRY DEVELOPMENT - พระครูพรหมเขตคณารักษ์; พระพิพิธพัชโรดม (Journal of MCU Phetchaburi Review, 2021)
The 20 - year National Strategy 2018 - 2037 discusses urban, rural, agricultural, and eco - industrial development. Aimed at developing infrastructure of the public and private sectors, Emphasis is continually growing urbanization by organizing a landscape plan for urban, rural, agricultural, and industrial development. Including conservation areas according to potential and unity of ecological suitability, conservation areas develop urban, rural, farming, and the eco - industrial regions. That is managed according to the sustainable environmental map, pollution that affects the environment. And chemicals in the agricultural sector to comply with international standards and international standards; preserve, conserve, restore and develop natural resources Architectural heritage and art, culture, identity and indigenous way of life-based on nature. And a sustainable cultural base Develop a network of urban and community development organizations, including a group of volunteers with the participation mechanism of all local sectors and strengthening the public health and environmental health system. And improve the ability to prevent emerging and recurrent diseases. In addition, the Master Plan under the Six National Strategy, Smart Living Areas and Cities, stated that urban, rural, agricultural, and eco-industrial development. With management accordingly, Sustainable Ecological Map Develop and develop a system for linkage, management, and analysis of big data for the national ecological mapping. Including supporting the direction according to the potential of the ecosystem and the preparation of city and rural planning According to the benchmark and composition of and overall city plan, land use, transport, public utilities, etc. The author is interested in the content. And information on urban, rural, agricultural, and eco - industrial development for further development and benefit of the students.